Financial impact of trust and institutional quality around the world - Svatopluk Kapounek; Evžen Kočenda; Luděk Kouba (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We investigate the financial impact of social trust, institutional quality, and regulations. As a testing ground we employ a unique, large, and hand-crafted dataset of more than 850 000 lending-based crowdfunding projects from 155 platforms across 55 countries during 2005-2018. We show that the impact of social trust is positive but economically less pronounced than that of institutional trust proxied by legal and property rights protection and regulation. Moreover, the financial impact of social trust is greater at the national level, while impact of institutional quality dominates at the international level. Nevertheless, the financial impact of trust and institutional quality around the world is positive, which is an encouraging implication under increasing anonymity and internationalization of financial environment.
Keywords: A13; D23; G41; K11; 330; social capital; social trust; institutional trust; uncertainty; crowdfunding; financial markets